ADAM-17/FHL2 colocalisation suggests interaction and role of these proteins in colorectal cancer. Issue 3 (March 2017) - Verset, Laurine; Tommelein, Joke; Decaestecker, Christine; De Vlieghere, Elly; Bracke, Marc; Salmon, Isabelle; De Wever, Olivier; Demetter, Pieter
FHL2 is a multifunctional scaffolding protein; its expression is associated with poor prognosis in colorectal cancer. ADAM-17 is a metalloprotease implicated in ectodomain shedding. FHL2 regulates ADAM-17 plasma membrane localisation, and FHL2 deficiency leads to decreased activity of ADAM-17 in mouse macrophages. Presence and relationship of the ADAM-17/FHL2 complex with colorectal cancer progression is unknown. We studied FHL2 and ADAM-17 expression in several colon cancer cell lines by immunocytochemistry and western blot. To highlight the interaction between both molecules, we used the Duolink ® kit for proximity ligation assay on SW480 cells. We also performed proximity ligation assay on biopsies and surgical specimens of colorectal adenocarcinoma and on matched normal mucosa. Furthermore, biopsies of colorectal adenoma with matched normal mucosa were selected. For quantification, pictures of the malignant, adenomatous and normal tissues were taken. Proximity ligation assay signals were quantified. Mean numbers of proximity ligation assay signals and of proximity ligation assay signals/nucleus were calculated. All cell lines showed FHL2 immunoreactivity; strongest positivity was observed in SW480 cells. ADAM-17 was expressed in all cell lines. Proximity ligation assay signals were present in SW480 cells. Quantitative analysis revealed that the interaction between FHL2 and ADAM-17 is more frequent in malignant than in normal tissue (p = 0.005). The mean number of ADAM-17/FHL2 proximity ligation assay signals was higher in colorectal adenocarcinoma than in adenoma with low-grade dysplasia (p = 0.0004). FHL2 interacts with ADAM-17 in normal, dysplastic and malignant colon epithelial cells. Colocalisation of these proteins is more frequent in malignant than in normal and dysplastic cells, suggesting a role for ADAM-17/FHL2 complex in the development of colorectal cancer.